Fasilitas Tarif Pajak Penghasilan untuk Perusahaan Terbuka - Pamungkas, Hanggoro (Bina Nusantara University, 2012)
Income Tax Rate Facility in Article 17 is an incentive for Listed Corporate Tax Payer, provides incentive to listed company selling its shares to public at least 40% of total shares and owned by at least 300 companies at 5% maximum ownership. The research done to find out the tax revenue contribution effect in Tax District Office from the tax rate facility in 2008-2009. Research methodes used are library research and field reserach collecting data from documents and interview, show Tax Office lost 1,95% of tax revenue in 2008, and 4,34% in 2009. Companies enjoy the tax facility in 2009 grow compare to 2008, from 60 to 65 Taxpayers, but in 2010 drop to 59 Taxpayers. Market capitalization influenced by the 2009 and 2010 raise to 87,59% and 60,80%. From potential tax revenue lost ratio and market capitalization growth, the tax facility is the right policy to speed up the nation economy. Contribution effect from the Income Tax Rate Facility, Article 17 in 2008-2009, still could be improved for listed companies by having the tax facility socializaion.